CO2 emissions embodied in China's export. Issue 8 (17th November 2019) - Huang, Rui; Lenzen, Manfred; Malik, Arunima
ABSTRACT: The reduction of CO2 emissions embodied in export will have an important role for China to achieve its CO2 emissions peaking target. In this study, we use input–output analysis to examine the embodied CO2 emissions in China's export to its top largest trading countries from 2008 to 2015. We find that China's exported CO2 emissions peaked in 2008. More than 70% of embodied CO2 emission were exported to only 20 countries, and CO2 emissions exported to developing countries have been increasing. High-energy consumption sectors contribute to CO2 emissions embodied in export significantly, such as Electricity, Gas and Water. We conclude that structural adjustment could be considered alongside technological improvements to curb China's growing CO2 emissions.